1924
DOI: 10.1084/jem.39.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Inhibitory Substances in Pneumococcus Cultures

Abstract: The known factors concerned in the autoinhibition of growth of pneumococcus are: 1. The accumulation of acid products of metabolism, resulting in unfavorable reaction changes in the medium. 2. The exhaustion of the nutritive substances of the medium. 3. Under certain cultural conditions the formation and accumulation of peroxide in the medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1924
1924
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Although evidence that S. pneumoniae was capable of killing S. aureus was published over 100 years ago (17,18), studies of the molecular mechanism(s) behind these epidemiological observations were reinitiated when the pneumococcal vaccine was licensed in early 2000 in developed countries. Pericone et al (19), and then other investigators, demonstrated that pneumococcal strains isolated from disease or carriage interfered with the growth of S. aureus in broth cultures.…”
mentioning
confidence: 99%
“…Although evidence that S. pneumoniae was capable of killing S. aureus was published over 100 years ago (17,18), studies of the molecular mechanism(s) behind these epidemiological observations were reinitiated when the pneumococcal vaccine was licensed in early 2000 in developed countries. Pericone et al (19), and then other investigators, demonstrated that pneumococcal strains isolated from disease or carriage interfered with the growth of S. aureus in broth cultures.…”
mentioning
confidence: 99%
“…As pointed out earlier in the present paper, simultaneously with the occurrence of peroxide in the medium the culture filtrates acquire the property of inhibiting growth. That the inhibition is dependent, in the case of Staphylococcus aureus at least, upon the presence of peroxide, is indicated by the fact that the same culture fluids, after the peroxide has been destroyed, suffice to support growth of this organism (6). By contrast the pneumococcus itself, of the same or of different type, is unable to grow in the filtrate of a culture in which it previously thrived.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that under certain conditions peroxide occurs in pneumococcus cultures (4,5) and that bacteriafree filtrates containing this compound promptly change solutions of catalase-free crystalline hemoglobin to methemoglobin. 1 Moreover, it has been shown (6) that when the filtrate of a broth culture of pneumococcus is reinoculated with pneumococcus visible growth does not occur, and that this is due to at least three factors: the first is the unfavorable pH of the filtrate; the second is the lack of sufficient nutritive substances; the third is the presence of a peroxide in the filtrate. It has been demonstrated that a hardier organism, as Staphylococcus aureus, will grow in pneumococcus filtrates despite the action of the first two factors; whereas, growth does not occur in filtrates containing peroxide.…”
mentioning
confidence: 99%